An Investigation of Impact of Debt Structure on the market value of Jordanian Transportation Companies - Massadeh, Deema D.; Khanji, Ibrahim Marwan; Al-Eitan, Ghaith N. (The journal of contemporary issues in business and government, 2021)
The objective of this paper is to investigate the impact of debt structure on the market value of transportationcompanies,debt structure was measured by both debt ratio and short term debt, while market value was measured by market share price. The paper conducted on the data of all the 12 transportation companies listed in Amman Stock Exchange. The study relied on multiple regression analysis to examine the impact of debt ratios on firm market value.The analysis result indicates thatmarket value is effected by debt structure significantly, both debt ratio andshort term debthad a negative impact on market value, and suggests that more debt is not always useful for market value.